2022
DOI: 10.3390/gels8030145
|View full text |Cite
|
Sign up to set email alerts
|

Compressive and Flexural Properties of Ultra-Fine Coal Gangue-Based Geopolymer Gels and Microscopic Mechanism Analysis

Abstract: Geopolymer gel that possesses advantageous features of fast setting, high strength, and good durability is increasingly used in civil engineering, including rapid retrofit projects, roadway, and other construction projects. Furthermore, geopolymer gel is also a green and economical material as it derives from solid wastes. In this study, activators with different sodium silicate modulus and alkali content were used to activate ultrafine coal gangue and slag powder to prepare coal-gangue-based geopolymers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It is noted that the gel transition time decreases with increasing amounts of calcium sulfoaluminate and gypsum additions [91] Prescription (supplement use) coal gangue and slag powder…”
Section: Name Of the Influencing Factormentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the gel transition time decreases with increasing amounts of calcium sulfoaluminate and gypsum additions [91] Prescription (supplement use) coal gangue and slag powder…”
Section: Name Of the Influencing Factormentioning
confidence: 99%
“…The macrostructure of concrete produced through the utilization of centrifugal compaction technology exhibits irregularities. In accordance with conventional categorization, it can be divided into the following three layers: internal, middle, and external [91]. The study in [69] is devoted to the investigation of the dependence of the processes of formation of cement gel and methods of the compaction of cement systems.…”
Section: Name Of the Influencing Factormentioning
confidence: 99%
“…The analysis showed that the optimal concentration of mixed activator was 18-20%. The optimal modulus is 0.6-0.8 [64,104]. Guo et al [98] proposed that the modulus of Na 2 SiO 3 affects the polymerization reaction.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Slag nanomodification of cement composites has already established itself as a promising and effective solution for improving the micro- and macrostructure of various characteristics of concretes, mortars, products, and structures composed of them [ 6 , 7 , 8 , 9 , 10 , 11 ]. At the same time, much attention is being paid to the parameters of slag grinding; its activation, including alkaline; its use in combination with other finely dispersed additives, for example, fly ash and nanosilica; as well as the processes of hydration and structure formation of Portland slag cement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%